Exploiting the predictive power of educated spheroids to detect immune-mediated idiosyncratic drug-induced liver injury: the case of troglitazone - Salomé Roux; Sara Cherradi; Hong Tuan Duong (Frontiers Media S.A., 2024)
Idiosyncratic drug-induced liver injury (iDILI) is a major concern in drug development because its occurrence is unpredictable. Presently, iDILI prediction is a challenge, and cell toxicity is observed only at concentrations that are much higher than the therapeutic doses in preclinical models. Applying a proprietary cell educating technology, we developed a person-dependent spheroid system that contains autologous educated immune cells that can detect iDILI risk at therapeutic concentrations. Integrating this system into a high-throughput screening platform will help pharmaceutical companies accurately detect the iDILI risk of new molecules de-risking drug development.